2018
DOI: 10.3389/fpsyg.2018.01335
|View full text |Cite
|
Sign up to set email alerts
|

“Last Supper” Predicts Greater Weight Loss Early in Obesity Treatment, but Not Enough to Offset Initial Gains

Abstract: Background: Many participants experience clinically significant fluctuations in weight before beginning a behavioral weight loss program. Pre-treatment weight gain, often referred to as the “last supper” effect, may limit total weight loss from the time of the pre-treatment screening visit and could be an indicator that a participant will respond poorly to behavioral intervention.Methods: Data were from the weight loss phase of a two-phase weight loss maintenance trial, in which 178 participants with obesity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(45 citation statements)
references
References 15 publications
8
31
6
Order By: Relevance
“…Although two other studies failed to find this relationship, pretreatment weight loss was associated with weight loss success when outcomes were compared to screening visit weight rather than baseline weight [1,3]. However, all previous studies observed the relationship between pretreatment weight change and weight loss over relatively short periods (i.e., 14 weeks and six months) [1,2,3]. In addition, previous samples were primarily female [1,2,3] and two were mostly White/Caucasian [1,2].…”
Section: Background Weight Loss Interventionmentioning
confidence: 91%
See 4 more Smart Citations
“…Although two other studies failed to find this relationship, pretreatment weight loss was associated with weight loss success when outcomes were compared to screening visit weight rather than baseline weight [1,3]. However, all previous studies observed the relationship between pretreatment weight change and weight loss over relatively short periods (i.e., 14 weeks and six months) [1,2,3]. In addition, previous samples were primarily female [1,2,3] and two were mostly White/Caucasian [1,2].…”
Section: Background Weight Loss Interventionmentioning
confidence: 91%
“…Participants identified gender (i.e., male, female), age (i.e., <30 years, 30-40 years, >40 years), ethnicity [i.e., (non-Hispanic/Latino, Hispanic/Latino)], and race [i.e., Caucasian, African American, and Other (i.e., race categories that were infrequently reported)] at SV. From SV to BV, individuals were categorized as those who lost weight (> 1.15% decrease), remained weight stable, and gained weight (> 1.15% increase) similar to previous studies [1,2,3]. This criterion is half of 2.3% used in research defining weight maintenance [7].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations